Meta-Analysis of Prostate-Specific Antigen and Digital Rectal Examination as Screening Tests for Prostate Carcinoma - Mistry, K.; Cable, G. (Journal of the American Board of Family Medicine, 2003)
Physicians commonly screen for prostate cancer by using prostate-specific antigen (PSA) and digital rectal examination (DRE). The usefulness of these screening mechanisms is not well established, however. A meta-analysis of PSA and DRE to detect prostate carcinoma was conducted with a focus on sensitivity, specificity, and positive predictive value. A literature search of OVID database (1966 to November 1999) using the medical subject headings "prostate-specific antigen" and "mass screening," as well as "prostate carcinoma," was performed. Thirteen articles were selected for the meta-analysis in this study. Most studies included asymptomatic men older than 50 years from various countries. Pooled results were calculated from the individual reports for sensitivity, specificity, and positive predictive value for PSA and DRE based on biopsy result as the reference standard. The overall detection rate of prostate carcinoma was 1.8% based on a positive biopsy. Of the prostate carcinoma detected, 83.4% was localized. The pooled sensitivity, specificity, and positive predictive value for PSA were 72.1%, 93.2% and 25.1%, respectively; and for DRE were 53.2%, 83.6% and 17.8%, respectively. There were two major outcomes of this meta-analysis. One was the potential for detecting early-stage prostate cancer with these screening tests, because 83.4% of total cancers detected were localized. The second important outcome was that the overall sensitivity, specificity, and positive predictive value for PSA were higher than those for DRE when used as a screening tool to detect prostate cancer. When a patient has abnormal findings using PSA and DRE, the chance of cancer is 1 in 4 or 5. Conversely, when findings from PSA and DRE are normal, the chance of missing a cancer is about 10%.